Calculation of Metrological Characteristics of pH Control System for Mixture of Acids and Alkalis - R. I. Vorobey; O. K. Gusev (Наука и техника)
The paper proposes a model of method to control a pH index of acid and alkali solution mixtures. This model is based on the measurement of the material amount in mixed solutions. It permits to calculate the required metrological characteristics of measuring channels.The calculation of admissible concentration and mass values of solutions to be mixed is given in the paper. The limits of admissible measurement error values are also calculated.It is shown that the proposed method that is to control a pH index is applicable for automation of technological neutralization processes of acids and alkalis contaminated by fine-disperse inclusions under conditions of industrial plants.